Educational Radio: Generator of Writing Processes - Castellanos Jaimes, Lenis Saida; Mayorga Suárez, Laura Isabel (Rastros Rostros, 2012)
This paper corresponds to the ongoing research “Didactic Use of a Children’s Radio Program for the Strengthening of the Writing Processes in First Grade Children”, held since 2011 as degree work of the Masters in Education at the Universidad del Tolima. It pretends to analyze the role educational radio as a generator of communication skills, specifically writing. This will address issues regarding listening skills, imagination, creativity and production of a text. It presents both a brief analysis of backgrounds in the categories of educational radio and writing processes, such as the methodological bias, the results and the partial conclusions of the research.